A Technical Modification for Establishing Selective Antegrade Cerebral Perfusion during Pulmonary Endarterectomy - Czerny, Martin; von Samson, Patrick; Passlick, Bernward; Beyersdorf, Friedhelm; Kroll, Johannes (The Thoracic and Cardiovascular Surgeon Reports, 2016)
Pulmonary endarterectomy (PEA) due to chronic thromboembolic pulmonary hypertension (CTEPH) is mainly performed in deep hypothermic circulatory arrest without additional cerebroprotective means. A 49-year-old man was treated by PEA for CTEPH by using selective antegrade cerebral perfusion by advancing the tip of the systemic perfusion cannula into the brachiocephalic trunk. The postoperative course was uneventful.
Keywords: pulmonary arteries; pulmonary endarterectomy; selective antegrade cerebral perfusion